(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Newly series of 6,6’-((2-(Aryl)dihydropyrimidine-1,3(2H,4H)-diyl)bis(methylene))bis(2-methoxy phenol) (3a-i) weresynthesized from cyclization of 6,6’-((propane-1,3-diylbis (azanediyl)) bis(methylene)) bis(2-methoxyphenol) with severalaryl aldehyde in the presence of acetic acid. The newly compounds characterized from their IR, NMR and EIMs spectra.The antioxidant capacity of these compounds screened by utilizing DPPH and FRAP assays. Compounds 3g and 3i exhibitedsignificant antioxidant capability in both assays. Docking study for these compounds as a potential inhibitors of gyrase enzymewere carried out. Compound 3g exhibited significant inhibition with binding free energies (DG) higher than novobiocin.compounds 2, 3a, 3b, 3f exhibited prominent DG.